Conception and methodology of controlling development in organizations oriented for result and innovations in conditions of Kazakhstan. (Journal of Economic Research & Business Administration, 2015)
In a market environment due to business growth, complicating the structure of the organization and the subsequent exacerbation of existing problems in it, there is a need for a new business model. Controlling development in theenterprises of the Republic of Kazakhstan contributes to the formation of the strategic and operational planning, timely calculation of risks and anticipating the challenges and obstacles, and provides transparency of enterprises. In order to solve all the issues involved the new approaches and implementation of advanced management techniques are required.
Keywords: controlling; organization; innovation management; business management techniques